2008
DOI: 10.1108/13612020810906128
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mall environment on female fashion shoppers' value and behaviour

Abstract: PurposeThe purpose of this paper is to explore how the shopping mall environment influences the shopping experience and approach behaviour of female fashion shoppers.Design/methodology/approachFemale shoppers were first clustered along the fashion orientation of the stores they patronise. Shoppers' response and behaviour was modelled in an invariant multigroup latent structural path analysis. Paths were initially constrained and then released as required. A total of 286 usable questionnaires were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 29 publications
3
58
3
2
Order By: Relevance
“…When a customer experiences positive emotions he/she represents higher levels of satisfaction in a service encounter (Sheng et al, 2011). In addition, shopping effect was found to have a positive impact on perceived value, which in turn positively influences a consumer's consistent repeat purchase behavior (Michon et al, 2008). Tourists with positive feelings are expected to experience higher levels of value.…”
Section: Hedonic Affect Customer Satisfaction and Perceived Valuementioning
confidence: 99%
“…When a customer experiences positive emotions he/she represents higher levels of satisfaction in a service encounter (Sheng et al, 2011). In addition, shopping effect was found to have a positive impact on perceived value, which in turn positively influences a consumer's consistent repeat purchase behavior (Michon et al, 2008). Tourists with positive feelings are expected to experience higher levels of value.…”
Section: Hedonic Affect Customer Satisfaction and Perceived Valuementioning
confidence: 99%
“…Carr (1990) posits that shopping motives range between pleasurable / hedonic to functional and malls that are able to deliver fun retail formats ( Cope, 1996 ;Burke, 1997 ;Wakefi eld and Baker, 1998 ) will be successful. Shopping malls have been of interest for researchers ( Goss, 1993 ;Robertson, 1995 ;Buss, 1997 ;Miller, 1998 ;Csaba and Askegaard, 1999 ;Castaldo and Botti, 2001 ;Yavas, 2003 ;Arnold and Reynolds, 2003 ;Resciniti, 2004 ;Rintam ä ki et al , 2006 ;Ahmed et al , 2007 ;Ooi and Sim, 2007 ;Michon et al , 2008 ;Teller et al , 2008 ) as they suggest a multitude of factors infl uencing consumers ' shopping behaviour.…”
Section: Mall Attributesmentioning
confidence: 99%
“…To attract consumers, malls are coupling traditional selling activity with other value-added services, which make malls retail-entertainment complexes ( Csaba and Askegaard, 1999 ;Stoel et al , 2004 ;Laroche et al , 2005 ;Michon et al , 2008 ). Carr (1990) posits that shopping motives range between pleasurable / hedonic to functional and malls that are able to deliver fun retail formats ( Cope, 1996 ;Burke, 1997 ;Wakefi eld and Baker, 1998 ) will be successful.…”
Section: Mall Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Priori segmentation approach employs consumer externalities such as age, sex among others to explain differences in consumer segments" behaviour. Following this school of thought, a number of studies have been conducted wherein gender (Michon et al 2008;Kuruvilla et al 2009), age (Anselmsson, 2006), or mother and daughter (Martin, 2009) were used to segment and explain consumer segments. Marketing academics have fiercely challenged priori methods because of its focus on external characteristics of consumers and a number of studies have suggested including other variables in explaining the differences between segments" behaviour (Gonzalez-Hernandez and Orozco-Gomez, 2012).Also, Harrison (1995) posits that consumer buying behaviour is not primarily dependent on those external characteristics.…”
Section: Review Of Related Literature: Prior Research On Predictors Tmentioning
confidence: 99%